Clavicle aseptic nonunion: is there a place for cortical allogenic strut graft?. (October 2017) - Rollo, Giuseppe; Vicenti, Giovanni; Rotini, Roberto; Abate, Antonella; Colella, Antonio; D'Arienzo, Antonio; Carrozzo, Massimiliano; Moretti, Biagio
Abstract: We investigated functional and radiological outcome in 57 cases of midshaft clavicle nonunion treated with open reduction and internal fixation with plate and screws over a 13 year-period. Intercalary bone graft was used in 42 patients; opposite autologous strut graft was used in 31 cases to provide mechanical support to the host bone. Patients were analysed using chart and radiological review and assessed with DASH questionnaire obtained at the latest follow-up. 37 patients were male while 20 were females, with a mean age of 35 years (63–17). All cases were of nonunion, 35 atrophic and 22 hypertrophic. The dominant side was injured in 32 cases and the non dominant in 25 cases. Primarily, 43 cases were treated conservatively with a figure of eight bandage. Time between fracture and our operative treatment was on average 44 months (13–72 months). Only those patients who were symptomatic were included in this study. We used straight reconstruction LCP and low profile precontoured plates. By reviewing patients charts all the cases but one of nonunion progressed to osseous healing at a mean time of 14 weeks (range 12–16). The patient with non-union refused further surgery. 49 patients were available for a final follow up. DASH score was 16.7 at an average of 42 months. Open surgery and internal fixation, using plate and screws in a compression construct is the treatment of choice for symptomatic clavicular non-unions. Intercalary autologous or allograft bone graft should be used especially in patient with significant bone loss; autologous cortical strut graft provides optimum mechanical stability, thus assuring optimal screw purchase and allowing immediate limb movement.